Conceptualization and Measurement of Flow in a Chinese Blended English as a Foreign Language Learning Context - Wang, Xin; Huang, Chenguang (Frontiers in Psychology, 2022)
This study takes a holistic view of flow and anti-flow experiences as interactive subsystems in blended English as a foreign language (EFL) learning and examines the dynamic complex construct in the field of instructed second language acquisition (ISLA). We first rephrased the 22-item Classroom Flow Questionnaire (CFQ) to better reflect the context of blended EFL learning. The modified CFQ was then administered to 661 first language Chinese EFL learners. A final 14-item Foreign Language Flow Scale (FLFS) was developed based on results from a series of reliability (e.g., item analysis, internal consistency, and test-retest reliability) and validity (e.g., construct validity, convergent validity, discriminant validity, and criterion validity) tests. Both exploratory and confirmatory factor analysis results have demonstrated that foreign language learning flow is a three-dimensional construct involving Enjoyment, Boredom, and Anxiety, thus conceptualizing and validating flow as a continuum with both positive and negative ends. Moreover, participants reported that they experienced the lowest degree of enjoyment, while with respect to the negative flow, they almost experienced similar degree of boredom and anxiety. The present study contributes to the development of the conceptual framework for flow in ISLA as well as constructive pedagogical implications for L2 researchers and educators. Suggestions for future research are also provided.